IMPLEMENTASI PEMBERIAN MAKANAN TAMBAHAN (PMT) BERBASIS PANGAN LOKAL DALAM PENANGGULANGAN STUNTING (STUDI KASUS ANAK USIA DINI DI DESA DUKUHLOR) - Eka Fitriyenti; Mira Mayasarokh (Jurnal Pelita PAUD, 2026)
The purpose of this study was to determine the implementation of local food-based supplementary feeding in overcoming child stunting in Dukuhlor Village. The local food referred to here is processed tubers (sweet potatoes, cassava, beans, corn, moringa, etc.). This study uses a qualitative research method with a case study approach. The data sources in this study are primary and secondary data sources. The sample of this study was taken using a purposive sampling technique. The research instruments were interviews, observations, and documentation. The implementation of providing additional food based on local food in Dukuhlor Village is expected to be one of the effective efforts to overcome child stunting, which can bring changes to reduce stunting rates in villages, especially in Dukuhlor Village where this research was conducted.